Analisis Kinerja Keuangan pada PT. Bank Pembangunan Daerah Nusa Tenggara Timur Periode 2019-2022 - Melda Mariana Poeh; Yunelci Seliamang; Martina Kaisriani Rupa (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The purpose of this study was to determine and analyse the ability of East Nusa Tenggara Regional Development Bank to make a profit and how much this company uses its funds to generate profits. This research method is descriptive with a quantitative approach. The analytical tools used in this study are Net Profit Margin, Return on Equity, Return on Assets, Operating Cost Ratio, Loan to Deposit Ratio, Loan to Asset Ratio, Primary Ratio and Debt to Equity Ratio. The results of research based on the Profitability Ratio on ROA and BOPO in 2019- 2022 show that the financial performance of Bank Pembangunan Daerah NTT can be said to be good. ROE has decreased from 2029- 2022 which shows a less healthy state. The Liquidity Ratio on LDR and LAR from 2019- 2022 shows a fairly healthy state. The Solvency Ratio on PR from 2019-2021 shows an unhealthy state and in 2022 it has increased significantly. Then DER from 2019- 2022 shows a very healthy state.